ETArch Pilot: Scaling up the Deployment of a Clean Slate Network Architecture at a Telecom Operator - Theodoro, Luiz Cláudio; Damaso, Pedro; Ribeiro, Rogerio F.; Silva, Flá vio; Frosi, Pedro; Mendes, Alex Vaz; Pereira, João Henrique de S. (Anais do Workshop de Pesquisa Experimental da Internet do Futuro (WPEIF); 2017: Anais do VIII Workshop de Pesquisa Experimental da Internet do Futuro, 2017)
Future Internet architectures is a response from the research community to the challenges that Internet architecture faces today, such as mobility. One major issue in this area is the deployment and test of them over large scale production networks. This work scales up the deployment of the clean-slate Entity Title Architecture (ETArch) on a production network of a telecom operator. Using Virtual Tunnel (VTun) as an overlay is was possible to connect different users in different cities at Minas Gerais state in Brazil. ETArch Pilot shows the feasibility to move toward future Internet deployment in order to bring new services and applications to users.